SUBCUTANEOUS PHEOHYPHOMYCOSIS CAUSED BY Phoma cava: REPORT OF A CASE AND REVIEW OF THE LITERATURE - Clarisse ZAITZ; Elisabeth Maria HEINS-VACCARI; Roseli Santos de FREITAS; Giovana Letícia Hernández ARRIAGADA; Ligia RUIZ; Silvia A.S. TOTOLI; Ana Cristina MARQUES; Gisele G. REZZE; Helena MÚLLER; Neuza Sakai VALENTE; Carlos da Silva LACAZ (Revista do Instituto de Medicina Tropical de São Paulo, 1997)
We report a case of subcutaneous pheohyphomycosis observed in a male patient presenting pulmonary sarcoidosis and submitted to corticosteroid treatment. He presented nodular erythematous-violaceous skin lesions in the dorsum of the right hand. Histopathological examination of the biopsied lesion revealed dematiaceous hyphae and yeast-like cells, with a granulomatous tissual reaction. The isolated fungus was identified as Phoma cava. A review of the literature on fungal infection caused by different Phoma species, is presented. The patient healed after therapy with amphotericin B, followed by itraconazole O presente trabalho registra um caso de feo-hifomicose subcutânea em paciente do sexo masculino com o diagnóstico de sarcoidose pulmonar, submetido à terapêutica por corticosteróides quando apresentou no dorso da mão direita lesões cutâneas nodulares, eritêmato-violáceas, de aspecto infiltrado, exigindo biópsia para o diagnóstico. O exame histopatológico revelou processo granulomatoso, com a presença de hifas e células arredondadas demácias. Cultivo positivo para fungo identificado com Phoma cava. Os Autores fizeram revisão da literatura sobre as infecções fúngicas provocadas por diversas espécies de Phoma, mostrando a raridade desta observação. A evolução foi favorável com a administração da anfotericina B (via venosa) seguida do itraconazol (via oral)